Students’ Entire Deep Learning Personality Model and Perceived Teachers’ Emotional Support - Liu, Enyun; Zhao, Jingxian; Sofeia, Noorzareith (Frontiers in Psychology, 2022)
In recent years, deep learning as the requirement of higher education for students has attracted the attention of many scholars, and previous studies focused on defining deep learning as the deep processing of knowledge of the brain, however, in the process of knowledge processing, the brain not only involves the deep processing of information but also participates in learning consciously and emotionally. Therefore, this research proposed a four-factor model hypothesis for deep learning that includes deep learning investment, deep cognitive emotional experience, deep information processing, and deep learning meta-cognitive. In addition, the research proposed teachers' emotional support perceived by students has an effect on the four factors of deep learning. Through SPSS26.0 and AMOS24.0, this research has verified the four-factor model of deep learning applying exploratory factor analysis(EFA) and confirmatory factor analysis(CFA) and verified that the perceived teacher emotional support has an impact on the four factors of students' deep learning using the structural equation model(SEM).